2014
DOI: 10.1093/database/bau002
|View full text |Cite
|
Sign up to set email alerts
|

NONATObase: a database for Polychaeta (Annelida) from the Southwestern Atlantic Ocean

Abstract: Networks can greatly advance data sharing attitudes by providing organized and useful data sets on marine biodiversity in a friendly and shared scientific environment. NONATObase, the interactive database on polychaetes presented herein, will provide new macroecological and taxonomic insights of the Southwestern Atlantic region. The database was developed by the NONATO network, a team of South American researchers, who integrated available information on polychaetes from between 5°N and 80°S in the Atlantic Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…Subsequent research greatly expanded our knowledge of the diversity and ecology of this group in the southern Atlantic (Nonato & Luna, 1970;ten Hove, 1975;Rullier & Amourex, 1979;Silva et al, 1980;Knight-Jones & Knight-Jones, 1991;Paiva, 1993;Santa-Isabel et al, 2000;Nogueira & ten Hove, 2000;Neves & Omena, 2003;Winston & Migotto, 2005;Assis et al, 2008Assis et al, , 2009Assis et al, , 2012Nogueira & Abbud, 2009;Skinner et al, 2012;Amaral et al, 2013;Schawn et al, 2016;Vieira et al, 2016). As a result of these efforts, the serpulid fauna in Brazil is known to number 43 species, of which only 14% are originally described for Brazil and the remaining 86% are considered exotic species (Amaral et al, 2013;Pagliosa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent research greatly expanded our knowledge of the diversity and ecology of this group in the southern Atlantic (Nonato & Luna, 1970;ten Hove, 1975;Rullier & Amourex, 1979;Silva et al, 1980;Knight-Jones & Knight-Jones, 1991;Paiva, 1993;Santa-Isabel et al, 2000;Nogueira & ten Hove, 2000;Neves & Omena, 2003;Winston & Migotto, 2005;Assis et al, 2008Assis et al, , 2009Assis et al, , 2012Nogueira & Abbud, 2009;Skinner et al, 2012;Amaral et al, 2013;Schawn et al, 2016;Vieira et al, 2016). As a result of these efforts, the serpulid fauna in Brazil is known to number 43 species, of which only 14% are originally described for Brazil and the remaining 86% are considered exotic species (Amaral et al, 2013;Pagliosa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen species of the genus Hydroides have been identified from along the Brazilian coast (Amaral et al, 2013;Pagliosa et al, 2014;Schawn et al, 2016;Ananias, 2017). Based on the results presented in Schwan et al (2016) and Amaral et al (2013), H. elegans and H. dirampha appear to be commonly found in Brazilian port zones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reefs of Phragmatopoma caudata Krøyer in M€ orch, 1863 are broadly distributed along the intertidal zone in the western Atlantic coastline, from Florida (USA) (34°N) to Santa Catarina (Brazil) (27°S), including many localities in the Caribbean (Kirtley, 1994). Although P. caudata reefs are known to exist at various locations along the Brazilian coast (Pagliosa et al, 2014), records in new localities continue to be reported. For instance, new reefs formed in Fortaleza (north Brazil) following the construction of a harbour (Fournier & Panizza pers.…”
mentioning
confidence: 99%
“…For example, Phragmatopoma caudata (the most abundant), is a gregarious Sabellaridae ecologically relevant in the construction of biogenic reefs what contribute to increase diversity and protect coasts (Goldberg, 2013;Nunes et al, 2017). In Brazil, there are records of Phragmatopoma caudata along the coast, from the Piauí State in the Northeast (Gomes-Filho et al, 2017) to the Rio Grande do Sul State in the South of the country (Kirtley, 1994;Lana and Bremec, 1994;Pagliosa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%